Intraoral approach to zygomatic fracture - Carvalho, Abrahao Cavalcante Gomes de Souza; Pereira, Cassiano Costa Silva; Queiroz, Thallita P.; Magro Filho, Osvaldo [UNESP] (Wolters Kluwer, 2012)
Abstract: The intraoral approach to zygomatic fracture treatment was introduced by Keen in 1909. This technique allows both an adequate visualization of the zygomaticomaxillary buttress and intraoral reduction of zygomatic arch fractures. Similar techniques have been published over the last 30 years. The aim of this study was to describe a modification of the Keen technique that promotes adequate visualization of the infraorbital rim and permits reduction and fixation of this region in cases of zygomatic fractures. The present technique has several advantages such as that (a) only 1 incision is necessary to approach the zygomaticomaxillary buttress and infraorbital rim, (b) it optimizes surgical time, and (c) it avoids periorbital scars. Fracture of the zygomatic complex is one of the most common facial traumas and has been extensively described in the literature.1 However, there are several controversies as regards the best technique and treatment of these fractures, such as closed versus open reduction; sequence of reduction and fixation in open techniques; complications; and morbidity rates of each technique. Currently, the intraoral approach for surgical treatment of zygomatic complex fractures has received special attention. It was first described by Keen in 1909, using the upper sulcus technique. Later, other studies showed different variations of this technique to reach the zygomatic arch and buttress.3,4 However, in most cases, infraorbital margin fixation was still performed through the subtarsal, subciliary, or transconjunctival approach. The purpose of this article was to describe the modifications made to the intraoral approach to allow reduction and fixation of the infraorbital rim in zygomatic fractures.
Keywords: Intraoral; Zygomatic fracture; Technique